PERTUMBUHAN ANTEROPOSTERIOR DAN VERTIKAL WAJAH PADA ANAK USIA SEKOLAH DENGAN STATUS GIZI BAIK BERDASARKAN USIA DAN JENIS KELAMIN (Kajian Secara Sefalometri Langsung pada Anak Suku Jawa di Desa Tamantirto Kecamatan Kasihan Kabupaten Bantul) - , Atiek Driana Rahmawati, Prof. Dr. Iwa Sutardjo RS, drg., SU., SpKGA(K). ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Facial human could be divided into three parts, upper, middle and lower. After birth, facial growth occured in three directions : transfersal, vertical and sagital (anteroposterior). The greatest vertical growth occured at the age of 7-11 years, and the sagital growth, the most intensive growth occured before and during the eruption of permanent molar. There was no significant correlation between growth pattern width at the maxillary sutura mediana with maxillary sutura height supporters. The growth in girls was two years earlier than in boys. The purpose of this study was to determine the relationship between anteroposterior and vertical facial growth and also the influence of the age and sex factors on school-age children with good nutritional status. Analytical observational research based on cross sectional research design was done on112 children from four elementary schools at Tamantirto Kasihan Bantul. The subjects were divided into14 groups according to their age and sex and each group consisted of 8 children. The measurements included the height of upper, middle and lower face, the length of the maxillary right and left, and the length of the mandibular right and left. Data were analyzed by Pearson correlation analysis, general linear model and canonical. The result showed that there were a weak positive relationship between middle face heigth and: maxillary right length (r=0,362), maxillary left length (r=0,278), mandibular right lenght (r=0,285), mandibular left lenght (r=0,334). There were weak relationships also showed between lower face height and: maxillary right lenght (r=0,236), mandibular right lenght (0,344), mandibular left lenght (r=0,383) and there is a very weak positive relationship between lower face height and maxillary left lenght (r=0,188).There was an influence of age on anteroposterior and vertical facial growth. Age and gender influence the anteroposterior and vertical growth of the face whereas the most influencing factor was the age factor on the growth of anteroposterior, this occured in boys ages 9, 10, 11 years and girls aged 6,9,11 and 12 years.